In What Ways Does Service Learning Enhance Young Investors’ Awareness of Social Responsibility In Investment? - Zahwa,; Khaerul Hakim,; Nur Syamsu,; Dewi Salmita ,; Imam A. J, (Journal of Community Service: In Economics, Bussiness, and Islamic Finance, 2025)
This community service project, titled “Service Learning for Young Investors: Strengthening Financial Analysis Competence and Social Responsibility in Investment in Central Sulawesi,” was conducted by the Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Datokarama Palu. The program was implemented through a Service Learning (SL) approach in collaboration with strategic partners  Bank Indonesia (BI) and the Indonesia Stock Exchange (IDX) involving participants from the Young Investor Community in Central Sulawesi. The project aimed to enhance participants’ competence in financial analysis while fostering awareness of social responsibility in investment practices aligned with Islamic economic values. Through a combination of workshops, mentoring sessions, and community-based investment simulations, students and young investors were directly engaged in real financial decision-making and ethical reflection. The results indicate that the Service Learning model effectively bridges theoretical understanding and practical experience, promoting not only analytical capability but also moral awareness and accountability in investment behavior. This program contributes to the development of socially responsible investors and serves as a model for integrating Service Learning into Islamic finance education in Indonesia.